The Value of Everything. Making and Taking in the Global Economy (an excerpt) - Мариана Маццукато (Journal of Economic Sociology, 2020)
According Prof. Mazzucato, to understand economic growth it is necessary to return to issues relating to what wealth means and where value comes from. The aim of this book is to reinvigorate the debate on value, which traditionally was—and should still be—at the core of economic thinking. Prof. Mazzucato points to the fact that in economics, various types of economic activities related to value extraction (or even value destruction) are camouflaged as or pretend to represent value creation. This results in a huge increase in social inequality and a significant decrease in investments in the real economy. Understanding the negative consequences of value extraction requires clarification of what is really taken. Which social, economic, and organizational conditions are necessary for value production? The Journal of Economic Sociology publishes “Introduction: Making versus Taking,” where Prof. Mazzucato makes distinctions between value making and value extraction (e.g. tax evasions, share buy-backs, etc.). It also defines “value creation” as the ways in which different types of resources are established and interact to produce new goods and services. Finally, the introduction provides details of how the book is structured.